EFFICIENCY ANALYSIS OF A WATER RESERVOIR ALTERNATIVE LINING - Furtini, A. C. C.; Lima, P. L. T.; Lima, L. A.; Thebaldi, M. S.; Abreu, L. H. P.; Monteiro, M. M.; Pinto, L. C. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Cost of lining reservoirs, whether for storage or water treatment, can be made it with different materials. As these structures have a relatively large surface area the investment amount can be economically unfeasible. A sustainable alternative method that can be used is the reduction of water infiltration in the soil, carried out through the use of a chemical dispersant such as Sodium Hydroxide (NaOH). Therefore, the aim of the present research was to define the lower NaOH concentration and volume to be applied in samples of a Red Latosol in the southern region of Minas Gerais state, Brazil. The samples, in triplicate, were treated with 5 NaOH concentrations (0, 5, 10, 15 and 30 g L-1) and 3 volumes per square meter application (5, 15 and 25 L m-2), submitting it to saturated hydraulic conductivity in constant head permeameters tests. The results showed that the application of different concentrations of NaOH reduced the saturated hydraulic conductivity in relation to the control treatment. The ratio of condutivity to NaOH concentration is best represented by the cubic regression y = 22.46 - 6.06x + 0.45x² - 0.01x³ (r² = 0.97). Regarding the different application rates, the difference was not significant indicating equality between the treatments analyzed. Therefore, the use of the 5 g L-1 of NaOH, applied at 5 L m-2, was economically more feasible and could therefore be a low-cost lining alternative.